A single extracellular amino acid in Free Fatty Acid Receptor 2 defines antagonist species selectivity and G protein selection bias. Issue 1 (December 2017) - Sergeev, Eugenia; Hansen, Anders; Bolognini, Daniele; Kawakami, Kouki; Kishi, Takayuki; Aoki, Junken; Ulven, Trond; Inoue, Asuka; Hudson, Brian; Milligan, Graeme
Abstract Free Fatty Acid Receptor 2 is a GPCR activated by short chain fatty acids produced in high levels in the lower gut by microbial fermentation of non-digestible carbohydrates. A major challenge in studying this receptor is that the mouse ortholog does not have significant affinity for antagonists that are able to block the human receptor. Docking of exemplar antagonists from two chemical series to homology models of both human and mouse Free Fatty Acid Receptor 2 suggested that a single lysine - arginine variation at the extracellular face of the receptor might provide the basis for antagonist selectivity and mutational swap studies confirmed this hypothesis. Extending these studies to agonist function indicated that although the lysine - arginine variation between human and mouse orthologs had limited effect on G protein-mediated signal transduction, removal of positive charge from this residue produced a signalling-biased variant of Free Fatty Acid Receptor 2 in which Gi -mediated signalling by both short chain fatty acids and synthetic agonists was maintained whilst there was marked loss of agonist potency for signalling via Gq/11 and G12/13 G proteins. A single residue at the extracellular face of the receptor thus plays key roles in both agonist and antagonist function.